Establishment and Development of Outer Space Legislation: Kazakh and Foreign Experience - KUANDYKOV, Bakhytzhan; AKHATOV, Ualikhan; TURSYNKULOVA, Dinara; ATAKHANOVA, Saltanat; ISABEKOV, Akylbek (Journal of Advanced Research in Law and Economics, 2017)
System analysis of base international law acts has been conducted in sphere of space activity, which shows that there is no specified distinct line between air and space areas. Actuality of such research determined by the necessity of upgrading of theoretical concepts, as also norms of modern international space legislation in reference to legal coverage delimitation of air and space areas. This necessity firstly caused by potential threats to national security and high probability of disputable situation appearance between subjects that are in space air relations, in specific for the fact of creation and usage of multiple time using space-air crafts (space-air objects), that can function in air and space areas. In the process of law enforcement subjects of space activity may face legal challenge application of air or space law while staying relevant aircraft in the airspace or outer space. It is shown that each country regulates space right in accordance with their own objectives of scientific and technological development. It was determined that for the countries of Southeast Asia's space program is a driver of development and structuring of all scientific and technological sectors. It is revealed that she is the greatest interest for South Korea because of the technical possibilities of improving and building space technology not only for their own use, but also on the orders of other countries. It was noted that it was in South Korea set up a sufficiently broad foundation for the integration of innovation in the overall structure of the economy and the use of space technologies will accelerate this growth. At the same time controls the legal field to fully contribute to the adoption of legal acts concerning the establishment of environment for development of the space industry.